Long Noncoding RNA SOX2-OT Exacerbates Hypoxia-Induced Cardiomyocytes Injury by Regulating miR-27a-3p/TGFβR1 Axis - Guang Yang; Chunsheng Lin (Cardiovascular Therapeutics)
Background. Myocardial infarction (MI) was a severe cardiovascular disease resulted from acute, persistent hypoxia, or ischemia condition. Additionally, MI generally led to heart failure, even sudden death. A multitude of research studies proposed that long noncoding RNAs (lncRNAs) frequently participated in the regulation of heart diseases. The specific function and molecular mechanism of SOX2-OT in MI remained unclear. Aim of the Study. The current research was aimed to explore the role of SOX2-OT in MI. Methods. Bioinformatics analysis (DIANA tools and Targetscan) and a wide range of experiments (CCK-8, flow cytometry, RT-qPCR, luciferase reporter, RIP, caspase-3 activity, trans-well, and western blot assays) were adopted to investigate the function and mechanism of SOX2-OT. Results. We discovered that hypoxia treatment decreased cell viability but increased cell apoptosis. Besides, lncRNA SOX2-OT expression was upregulated in hypoxic HCMs. Hereafter, we confirmed that SOX2-OT could negatively regulate miR-27a-3p levels by directly binding with miR-27a-3p, and miR-27a-3p also could negatively regulate SOX2-OT levels. Furthermore, knockdown of SOX2-OT promoted cell proliferation, migration, and invasion, but limited cell apoptosis. However, these effects were reversed by anti-miR-27a-5p. Besides, we verified that miR-27a-3p binding with the 3′UTR of TGFBR1 and SOX2-OT regulated TGFβR1 level by collaborating with miR-27a-3p in HCMs. Eventually, rescue assays validated that the influence of SOX2-OT silence or miR-27a-3p overexpression on cellular processes in cardiomyocytes injury was counteracted by TGFBR1 overexpression. Conclusions. Long noncoding RNA SOX2-OT exacerbated hypoxia-induced cardiomyocytes injury by regulating miR-27a-3p/TGFβR1 axis, which may provide a novel insight for heart failure treatment.